Evaluasi Beban Kendaraan Terhadap Derajat Kerusakan dan Umur Sisa Jalan (Studi Kasus: Jalan Pematang Raya-Siantar) - Ruhut Gerald Pasaribu; Adita Utami (Jurnal Teknik Sipil, 2024)
Road damage due to excessive vehicle load on Pematang Raya - Siantar Road threatens regional transportation and economy. This study evaluates the relationship between vehicle load and road damage to recommend more effective supervision. Secondary and primary data are used to analyze traffic growth, excess load, Vehicle Damage Factor (VDF), degree of road damage, and remaining life of the road. The results showed that the micro truck vehicle type had the highest excess load percentage (33.96%). Pematang Raya - Siantar Road experienced a decrease in the design life of 2.43% per year under normal load conditions. Still, under actual load conditions, it showed a decrease in the design life of 25.36%, reducing the road life to 7.20 years with a truck factor (TF) value reaching 1.3. Based on the research results, it is recommended to improve supervision and implementation of the Heaviest Axle Load (MST), repair road pavement layers, conduct periodic socialization and raids, utilize sensor technology, and conduct economic analysis to determine the financial impact of road damage.